2020
DOI: 10.1007/s11432-019-2660-3
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-concave optimization of secrecy redundancy rate in HARQ-CC system

Abstract: In a hybrid automatic repeat request with chase combining (HARQ-CC) system, we analyze physical layer secure performance and determine the secrecy redundancy rate by proposed quasi-concave optimization methods with effective secrecy throughput (EST) criteria. First, key performance metrics, including connection outage probability (COP), secrecy outage probability (SOP), EST, and delay, are discussed. Then, under the constraint of COP, we optimize the secrecy redundancy rate to maximize the EST, which is a quas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Most related works have not considered the influence of SOP in secrecy throughput, but this has been found to be inaccurate [24]. Hence, we define the effective secrecy throughput (EST) of a secure HARQ-CC system as [26]…”
Section: Security Performance Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most related works have not considered the influence of SOP in secrecy throughput, but this has been found to be inaccurate [24]. Hence, we define the effective secrecy throughput (EST) of a secure HARQ-CC system as [26]…”
Section: Security Performance Metricsmentioning
confidence: 99%
“…However, most of them did not consider the influence of secrecy outage on secrecy throughput, which generally led to overestimated performance [24]. Hence, in our previous work, we extended the effective secrecy throughput (EST) of a single transmission [25] into a HARQ-CC system with a passive eavesdropper, and optimized secrecy redundancy rate for improved security [26]. Nevertheless, another common scenario, which includes multiple eavesdroppers, rate adaption and limited latency, has not yet been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Mheich et al designed a rate adaptive secure HARQ scheme [ 29 ], and Guan et al addressed the reliability–security trade-off and accurate secrecy throughput [ 30 ]. It has been demonstrated that an eavesdropper cannot obtain the same diversity gain as a legitimate user, since re-transmissions rely solely on the latter user [ 31 ]. As another import metric, effective secrecy throughput (EST) with multiple eavesdroppers has been optimized in secure HARQ transmissions [ 32 ].…”
Section: Introductionmentioning
confidence: 99%